2022
DOI: 10.3390/pathogens11111332
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Implications of Shiga Toxin-Producing E. coli in Farm and Wild Ruminants

Abstract: Shiga-toxin-producing Escherichia coli (STEC) is a food-borne pathogen that causes human gastrointestinal infections across the globe, leading to kidney failure or even death in severe cases. E. coli are commensal members of humans and animals’ (cattle, bison, and pigs) guts, however, may acquire Shiga-toxin-encoded phages. This acquisition or colonization by STEC may lead to dysbiosis in the intestinal microbial community of the host. Wildlife and livestock animals can be asymptomatically colonized by STEC, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 256 publications
0
8
0
Order By: Relevance
“…In recent years, non-O157:H7 STEC serotypes associated with foodborne outbreaks and human infections have increased ( Valilis et al, 2018 ), thus information about virulence and pathogenesis of STEC strains in diverse ecological niches is desired for the development of effective mitigation strategies. Wildlife has been recognized as a primary source of emerging infectious diseases, and these animal reservoirs can harbor uncommon or uncharacterized serotypes ( Kim et al, 2020 ; Ray and Singh, 2022 ). Although all STEC strains have the potential to pose health risks, acquisition of certain virulence traits would promote the emergence of strains with a high-risk to human health.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, non-O157:H7 STEC serotypes associated with foodborne outbreaks and human infections have increased ( Valilis et al, 2018 ), thus information about virulence and pathogenesis of STEC strains in diverse ecological niches is desired for the development of effective mitigation strategies. Wildlife has been recognized as a primary source of emerging infectious diseases, and these animal reservoirs can harbor uncommon or uncharacterized serotypes ( Kim et al, 2020 ; Ray and Singh, 2022 ). Although all STEC strains have the potential to pose health risks, acquisition of certain virulence traits would promote the emergence of strains with a high-risk to human health.…”
Section: Discussionmentioning
confidence: 99%
“…Under certain conditions, isolation-independent approaches are promising and could be applied in the case of ambiguous results that render decision making difficult, particularly when the STEC strain cannot be isolated. Many studies on STEC prevalence in cattle have been conducted but none on STEC prevalence compared to background E. coli [ 40 , 41 ]. Such studies would give insights into the application of long-read metagenomic approaches to characterize STEC among other E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of STEC to humans can occur through the ingestion of contaminated meat or water, contact with animal feces, or person-to-person contact [8]. It has been observed that E. coli infections in animals can be asymptomatic; therefore, wildlife may be a natural reservoir of these pathogens, leading to an increased risk of zoonosis [14].…”
Section: Introductionmentioning
confidence: 99%